Application of Walkability Principles of Pedestrian Path in Supporting the Green City Concept (Case of Parasamya Street Corridor, Sleman Regency) - Suminar, Lintang; Kusumaningrum, Lia (Universitas Negeri Yogyakarta, 2022)
The convenience of pedestrian paths is an essential aspect that needs to be studied in urban planning. Along with the increasing use of motorized vehicles, facilities for pedestrians must also be considered to minimize the acquisition of pedestrian space. Walkability is a concept that prioritizes safety, comfort, and being able to provide friendliness to its users. The provision of facilities on pedestrian paths is also one of the supporting aspects in realizing a green city because the green lanes found on pedestrian paths have benefits such as circulation, city aesthetic functions, and maintaining urban air quality. The government area of Sleman Regency is an integrated office area that has begun to improve the pedestrian path, including Parasamya Street. This study aims to examine the application of the walkability principle on Parasamya Street, Sleman Regency, as an effort to support the concept of a green city. The research method used is qualitative through observation, documentation, mapping, and interpreting the results descriptively by comparing the existing conditions with theories and regulations related to the concept of pedestrian paths and the concept of a green city. The results obtained from this study are that the application of the walkability principles on Parasamya Street can support the concept of a green city which is indicated by the fulfilment of infrastructure facilities, including ecological comfort. Things that need to be improved are an equal distribution of facilities for the disabled and the improvement of crossing facilities.